The Post-Discharge Growth of Very Low Birth Weight Preterm Infants - Tuba Ozdemir; Abdullah Baris Akcan; Munevver Kaynak Turkmen (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In the present study, we investigate the growth characteristics of very low birth weight premature infants of up to two years corrected age, considering the factors affecting growth and catch-up growth time.